Proceedings of the 17th International Conference on Pattern Recognition, 2004. ICPR 2004. 2004
DOI: 10.1109/icpr.2004.1333735
|View full text |Cite
|
Sign up to set email alerts
|

Thermal face recognition over time

Abstract: We present a comparative study of face recognition performance with visible and thermal infrared imagery, emphasizing the influence of time-lapse between enrollment and testing images. Most previous research in this area, with few exceptions, focused on results obtained when enrollment and testing images were acquired in the same session. We show that the performance difference between visible and thermal recognition in a time-lapse scenario is smaller than previously believed, and in fact is not statistically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 8 publications
2
21
0
Order By: Relevance
“…On the other hand, outdoor recognition performance is worse for both modalities, with a sharper degradation for visible images regardless of the algorithm. In [15], the same authors conclude that recognition based on thermal images does not imply a less visible performance than when several weeks have elapsed between enrollment and testing.…”
Section: Image Signalsmentioning
confidence: 86%
“…On the other hand, outdoor recognition performance is worse for both modalities, with a sharper degradation for visible images regardless of the algorithm. In [15], the same authors conclude that recognition based on thermal images does not imply a less visible performance than when several weeks have elapsed between enrollment and testing.…”
Section: Image Signalsmentioning
confidence: 86%
“…Research has been conducted on whether these problems could be overcome by extending the systems with a thermal sensor. [166] shows a significant improvement by fusing the visible and thermal images in a time-lapse experiment. Work has been done on face recognition using both pixel-level fusion [127, 97,19], feature-level fusion [167], and decision-level fusion [145,129,29].…”
Section: Image Fusionmentioning
confidence: 96%
“…Some studies over a lengthy time interval were reported for face recognition. In [13] images of 240 distinct subjects were acquired under controlled conditions, over a period of ten weeks. They showed that there was not a clearly decreasing performance trend over a period of ten weeks and concluded that degradation line is small enough as to be nearly flat over this time period.…”
Section: Introductionmentioning
confidence: 99%